EVALUATION OF INJECTABLE IRON SUCROSE THERAPY IN CHILDREN WITH IRON DEFICIENCY ANEMIA: Injectable Iron Sucrose in Iron Deficiency Anemia - Malik, Nazir Ahmed; Shah, Sajid Ali; Mashhadi, Syed Fawad (Pakistan Armed Forces Medical Journal, 2016)
Objective: The study was designed to evaluate the response of intravenous iron therapy in children who were unable to tolerate oral iron.Study Design: Quasi experimental study (pre and post treatment design).Place and Duration of Study:The study period extended over a period of 2 years from Apr 2011 to Apr 2013 and was carried out in Combined Military Hospitals Okara and Panu Aqil cantt.Material and Methods: One hundred and forty two children selected through non probability purposive sampling having iron deficiency anemia were included in the study. Iron deficiency anemia was diagnosed by measuring hemoglobin (Hb), red cell indices like mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC) and serum ferritin. Total iron deficit was calculated using the formula: Total iron deficit (in mg) = Body weight (kg) x (target hemoglobin-actual hemoglobin) {gm/dl} x 2.4 + depot iron (mg). Dose of iron sucrose to be given i/v (ml) = Total iron deficit/2o mg. Pre treatment and three months post treatment mean Hb levels were compared in the sample and stratified according to gender.Results: Out of 142 patients 87 (61%) were males and 55 (39%) were females. Mean Hb before treatment was 7.85 ± 0.78 gm/dl while three months post treatment mean Hb was 10.29 ± 0.89 gm/dl (p